Netværksstyring af e-government - Löfgren Karl (Politik, 2012)
This aim of a more integrated e-government, which goes beyond the establishment of ’single’ governmental websites, calls for both horizontal, as well as vertical integration of otherwise separate public agencies and au- thorities who are supposed to collaborate towards ’joint’ and ’needs-based’ electronic solutions to the bene t of citizens. Consequently, many of the current endeavours of integrating government information systems is best described in terms of ’network governance’ in which interdependent, yet autonomous, agents through in- stitutionalised network arrangements, are in charge for the actual implementation of the policy. While many authors have described this implementation processes in purely technical interoperability terms, the article frames this development as a policy process of governing self-regulating networks. is paper is primarily a theoretical think piece in a systematic framework for the analysis of meta-governing the policy process of electronic government is presented. In addition to the value of presenting a more systematic framework of di erent forms of governing network, it seeks to discuss these forms also sheds light on whether or not the on-going process of vertical and horizontal integration leads to centralisation, and also how it can enhance our chances for better democratic control and accountability. Our arguments will be supported by empirical illustrations mainly adopted from Scandinavian research.